An improved method for pollen release from anther: a case study with mangroves. Issue 4 (1st October 2016) - Xiao, Lin; Yang, Qiong; He, He; Zhao, Jiangang; Ye, Changpeng; Wu, Yuanling; Han, Boping
Abstract: The estimation of pollen production is widely used in pollination and reproductive ecology, aerobiology and pollen-vegetation relationship studies. Pollen release is the key step in estimating pollen production and therefore, the technique used to release pollen is critical. Three methods, the drying method (DM), mechanical method (MM) and chemical method (CM), are used to determine the amount of pollen released from anthers. Few studies have compared the results obtained from each method, making it difficult to determine which method is most appropriate in a given situation. In this study, we compared existing methods with a new method that increases the amount of pollen released from anthers. Eight species of mangrove trees from the Neilingding-Futian National Nature Reserve were selected for study. We combined the MM and CM to produce a new method (the ultrasonic method, UM). To determine the best ultrasonic treatment time using the UM, different durations were tested and the various responses were analysed. The relationships between pollen rupture and the ultrasonic treatment time, pollen size, exine thickness and aperture size were analysed. Finally, four methods for pollen release from anthers were compared. The results indicated that the UM could be an efficient method to release pollen from the anther. To avoid pollen rupture, ultrasonic treatment times in the UM should be less than 30 s. The pollen rupture rate was significantly correlated with the ultrasonic treatment time ( r  = 0.618, p  < 0.001) and the aperture size ( r  = 0.248, p  = 0.036). This comparative experiment indicated that the UM can generate a greater pollen yield than other methods while causing less pollen rupture than the MM. Therefore, the UM may be suitable for more plant species and more accurate for pollen production estimates than the existing three methods, particularly when estimating pollen production in all community plants.